The incidence of peripheral nerve injuries related to patient positioning during roboticassisted surgery: An evidence summary - Tina Oblak; Brigid Gillespie (Journal of Perioperative Nursing)
Objective: To describe the incidence and anatomical locations of peripheral nerve injuries (PNIs) related to patient positioning during urologic, gynaecologic and colorectal robotic-assisted surgery (RAS).